Experiences of Turkish Cypriot, Kurdish and Turkish Youth in Creating Transnational Social Spaces in London Schools - Simsek, Dogus (Border Crossing, 2013)
This paper focuses on the role of school in identity formation of Turkish Cypriot, Kurdish and Turkish youths (thereafter TCKT) living in London and explores the perceptions of young people about their school life, mainly focusing on secondary school experiences, and exploring the difficulties faced in their relations with peers. It also examines the forms of homogeneity and heterogeneity within the school environment, examining their influence on identity formation and the negotiation of transnational social spaces by TCKT youth. The homogeneity of schools in London prevents them from forming identities based on interaction with various cultures and, therefore, limits their ability to create transnational social spaces.